Environmental Regulations of the Mining Industry: Two Case Studies from Western Australia - Govinnage, Sunil Kantha (Curtin University, 2018)
The study analyses the Western Australian mining regulatory framework of environmental compliance. Through the case studies of Yeelirrie uranium mining approval, and Collie coal mining, it identifies a dichotomy (Acts of Parliament and State Agreements) of mining legislation and multi-agency approach challenging effective environmental protection. Grounded in sustainability and social sciences approaches, the thesis draws from expert interviews to identify weaknesses and best practices. It makes recommendations for strengthening the implementation of the mining regulatory framework.